The Whimsic Alley book of spells : mythical incantations for wizards of all ages - Beahm, George W.; Goldin, Stanley, 1950- (Charlottesville, VA : Hampton Roads Pub. Co., 2007)
Provides more than 200 spells contributed by Harry Potter fans worldwide, as well as guidance on selecting an appropriate wardrobe, a history of wands, and other related topics.
What you need to know about this book / by George Beahm -- A history of Whimsic Alley ; Magiques and maglinots / by Stan Goldin -- Spells. Love and emotion spells ; Practical spells ; Time, space, and weather manipulation spells ; Dueling spells ; Communication spells ; Miscellany spells ; Whimsic Alley spells -- Wizard wears, wares, and where? / by Stan Goldin -- Wizard wear : assembling a wizarding wardrobe ; Creating a bewitching wardrobe ; Wizard wares : wands ; Wizard where? A visit to Whimsic Alley -- Extracted chapters from the Whimsic Alley Book of Knowledge / by Stan Goldin -- Where do wands come from? ; Mastering a spell ; Spells, charms, hexes, curses, and jinxes.
Keywords: Magic -- Fiction; Wizards -- Fiction; Witches -- Fiction; Fantasy